Melasma removal using Q-Switched Neodymium-doped Yttrium Aluminium Garnet laser toning and high-intensity focussed ultrasound - Shahad Abdulhadi; Mustafa Salih Al Mousawi; Wissam Majeed Kattoof (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the effectiveness of combining high-intensity focussed ultrasound and a Q-switched neodymium-doped yttrium aluminium garnet 1064nm low-fluence toning laser in the treatment of melasma. Method: The experimental study was conducted from November 2020 to August 2021 at the medical physics laboratory, College of Medicine, Mustansiriyah University, Baghdad, Iraq, and comprised individuals of either gender aged >25 years having mixed form melasma in malar and forehead areas. Each participant received high-intensity focussed ultrasound treatment on the right side. After 2 weeks, Q-switched neodymium-doped yttrium aluminium garnet 1064nm low-fluence toning laser was applied to the melasma patches 4 times at one-week intervals. Melasma area and severity index scores were noted at baseline and at each visit for each patient. Visual analogue scale was used for objective evaluation. After the 4 laser sessions, all the patients completed a 3-month follow-up. Data was analysed using SPSS 24. Results: Of the 25 subjects, 15(60%) were females and 10(40%) were males. The overall mean age was 41.6±8.46 years (range: 22-60 years). There was a significant improvement with high-intensity focussed ultrasound (p<0.05). In the 3rd laser session, there was a significant difference in melasma area and severity index score of 2.48 for the right side and 3.12 for the left side (p<0.05). In the 4th session, there was a significant difference in melasma area and severity index score of 1.68 for the right side and 2 for the left side (p<0.05). No post-inflammatory hyperpigmentation or rebound was noted. Conclusion: High-intensity focussed ultrasound combined with toning laser was more effective than Q-switched neodymium-doped yttrium aluminium garnet 1064nm low-fluence laser alone in removing difficult melasma from the malar area in the 2nd, 3rd and 4th sessions, and from the forehead in the 3d and 4th sessions. Key Words: Aluminum, Neodymium, Melanosis, Yttrium